Antibiotic resistance in Bartonella bacilliformis clinical isolates from an endemic area of Peru - Silva-Caso, Wilmer (2015)
Bartonella bacilliformis is a facultative, intracellular, aerobic, Gram-negative coccobacillus causing the so-called Carrión's disease, a human infection endemic to specific areas mainly inhabited by low-income communities of Peru but also present in other Andean communities. It is considered a truly neglected tropical disease and is transmitted through the bite of female sandflies of the genus Lutzomyia [1]. Carrión's disease has two different clinical presentations; an initial febrile and haemolytic anaemia phase, known as Oroya fever, which has a mortality rate ranging from 44% to 88% in untreated patients; and a second phase characterised by the development of dermal eruptions known as Peruvian wart [1,2].